The Development Project Based-Learning Food Microbiology E-Module Based on The Study of Kombucha Fermentation - Lianto Lianto; Sri Rahayu Lestari; Hendra Susanto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This research is research and development based on Lee and Owens’ design that aims to develop a valid and practical food microbiology electronic module based on Project-Based Learning (PjBL). The research and development consisted of five steps: analysis, design, development, implementation, and evaluation. The validity of e-module was assessed by content expert, media and teaching material expert, and biology education practitioner. The practicality of e-module was assessed by The State University of Malang students who had joined food microbiology course. The instruments of this research were validation sheets of content expert, media and teaching material expert, biology education practitioners, and student questionnaire sheet responses. The development outcome showed that the validation of the content experts, media and teaching, and biology education practitioner give a percentage of 100%. The outcome of the practicality of e-module showed that the individual trial gets a percentage of 92,44%, small group is 90,96%, and the field is 92,96%. According to the outcomes, it can be inferred that e-module have filled the validity and practicality necessity to be applied as teaching material in food microbiology courses.